Optimizing Storage Tank Size for Improved Reliability of Roof Rainwater Harvesting Systems: The Case of Goba Ward, Dar es Salaam - Nobert, Joel (Tanzania Journal for Population studies and Development, 2026)
Residents in most parts of Dar es Salaam experience challenges in trying to get a stable supply of water. Roof-based rainwater harvesting has found a widespread adoption as one of the alternative sources to reduce water shortage in households, and has been used in sustainable urban drainage system, due to its effectiveness in dampening flood risks. However, most of the existing rainwater harvesting systems are not tailored to household requirements; instead they are built based on the availability of space and one’s financial capability. This article analyses the reliability of the existing rainwater harvesting systems in Goba Ward, Dar es Salaam, using a daily water balance model. The article also evaluates the required optimum storage needed to meet a certain demand for the existing roof area and rainfall characteristics. Existing tank capacities, roof areas, and household size were obtained through a household survey. The study results show that the existing storage capacities are underestimated and, in some cases, overestimated compared to the simulated optimum storage; thereby resulting in performance inefficiencies. The methodology to determine the optimum size of the storage tanks was suggested by considering daily demand, roof area, and reliability desired;thus providing a usable toolto enhance design systems while considering local climate. The study recommends the development of standardized guidelines for optimizing rainwater harvesting storage capacity based on local rainfall variability, roof catchment area, and household water demand conditions.